Uncovering Lecturers' Perceptions of the Contextual Teaching and Learning (CTL) Approach for Teaching Reading in Two Different Institution Contexts - Samsudin, Samsudin (Journal for Teaching and Education for Scholars, 2025)
This study investigates the perceptions and experiences of educators regarding the implementation of Contextual Teaching and Learning (CTL) in reading instruction across diverse educational contexts. Utilizing a qualitative research design, including multiple case studies, data were collected through interviews with three experienced lecturers. Thematic analysis revealed insights into lecturers' interpretations of CTL, their experiences in its implementation, approaches to selecting teaching materials, challenges encountered, and perceived benefits. Findings indicate varying interpretations of CTL, emphasizing the importance of tailoring lessons to students' interests and backgrounds. Lecturers demonstrated how CTL fosters active participation and engagement, particularly using culturally relevant materials. Challenges such as limited resources and low English proficiency required multifaceted solutions. Nevertheless, lecturers unanimously recognized CTL's effectiveness in enhancing student learning outcomes and fostering meaningful learning experiences. This study advances knowledge about the potential of CTL to strengthen reading instruction and guides curriculum writers, educators